Faktor Determinan Yang Mempengaruhi Upaya Penghindaran Pajak - Febri Handaru Putri; Iman Akhadi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to obtain empirical evidence approximately the effect of independent variable consisting of leverage, profitability, sales growth, audit committee, company size and company age towards the dependent variable tax avoidance. The object of research is a manufacturing company listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. The number of samples in this research is 55 companies with a total of 165 research data that match the criteria using purposive sampling method. This research uses multiple regression analysis method consisting of descriptive statistics, normality tests, outlier tests and classic assumption tests. The end result of this research are audit committee has impact on tax avoidance. It can be explained that the higher the number of audit committees in the company, the better the quality of good corporate governance. This will minimize the occurrence of tax avoidance practices While other independent variable consisting of leverage, profitability, sales growth, company size and company age has no impact on tax avoidance.